The Antimicrobial and Antioxidant Effects of Grapefruit (Citrus paradise) Peel Extract - Osama H. Abed; Mohammad Hussein AlAubaidee; Ahmed L. Azzawi; Hasan N Alabbasy (Genius Journals, 2022)
Phytochemicals are natural compounds found in different parts of the plant (seeds, fruit, peel, rout, etc.). Phytochemicals can exhibit a therapeutic property for many health problems including cardiovascular and metabolic disorders. Grapefruit (Citrus paradise) is one of the citrus family that are grown in different countries around the world. The documents have shown the abundance of many phytochemicals in the grapefruit including polyphenols, flavonoids, carotenoids, and vitamins. We have aimed to prepare two extracts of the grapefruit peels, one ethanolic extract and one concentrate oil of the peels. The antimicrobial and antioxidant properties of the two extracts were experimented. The peel extract of the fruit has shown a great potential in the inhibition of bacterial strains, fungus and scavenging the free radicals. The concentrate oil extract of the grapefruit peels has shown antioxidant properties that are close to the pure ascorbic acid with maximum inhibitory effect against E. coli, S. epidermidis and S. aureus. While the antioxidant properties of the ethanolic extract of grapefruit peel were much lower than the concentrate oil or ascorbic acid, it still a good choice with a best linear association. Furthermore, ethanolic extract has shown a maximum inhibitory effect against the growth of klebsiella sp. and C. albicans which may be attributed to the characteristics of the solvent
Keywords: Citrus paradise; phytochemicals; DPPH; antibacterial